Acrylic resin, preparation method and application thereof, lithium ion battery negative electrode slurry and negative electrode plate
By using an acrylic resin composed of a variety of monomers and crosslinking agents as a thickener in the graphite negative electrode of lithium-ion batteries, the problems of long glueing time, low bonding strength and poor flexibility of CMC thickener are solved, and the high peel strength and cracking resistance of the electrode sheet are achieved, and the cycle life of the battery is extended.
Patent Information
- Application Number
- CN202411972943.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-25
AI Technical Summary
The existing lithium-ion battery graphite negative electrode thickener CMC has problems such as long glueing time, low bonding strength and poor flexibility, resulting in poor processing performance of the electrode sheet and obvious volume expansion effect, which in turn affects the cycle life of the battery.
An acrylic resin composed of Class A monomer, Class B monomer, Class C monomer and crosslinking agent is used as a thickener, and is prepared by precipitation polymerization method to optimize the monomer ratio and polymerization reaction conditions to improve the adhesion and flexibility of the resin.
The acrylic resin exhibits good thickening and dispersing effects in the graphite negative electrode slurry, significantly improving the peel strength of the electrode sheet and thick coating anti-cracking performance, and extending the cycle life of the battery.
Smart Images

Figure CN119684507A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an acrylic resin, a preparation method and application thereof, a negative electrode slurry and a negative electrode sheet of a lithium ion battery. Background Art
[0002] In the manufacturing process of lithium-ion batteries, negative electrode thickeners are an indispensable type of polymer materials. Their main function is to disperse the negative electrode slurry evenly and prevent the slurry from settling; at the same time, they also bond the negative electrode active material to the current collector to maintain the stability of the pole piece structure. At present, for the graphite negative electrode system, the thickener is sodium carboxymethyl cellulose (CMC). CMC is an anionic water-soluble polymer obtained from cellulose as a raw material. It has excellent viscosity, water absorption and water retention. At the same time, it has extremely high slurry stability, which can ensure the stable processing of the negative electrode pole piece. At present, in the graphite negative electrode system, CMC is used in combination with styrene-butadiene rubber (SBR) to form a binder system, but the CMC+SBR system has the disadvantages of long glue application time, low bonding strength, and poor flexibility. While ensuring the viscosity, dispersibility and stability of the negative electrode slurry, improving the flexibility and mechanical properties of the thickener, thereby improving the processing performance of the pole piece and inhibiting its volume expansion effect, and extending the cycle life of the battery are key technical issues that need to be solved at present. Therefore, designing a new polymer to replace CMC and solve the above problems is the goal of engineers.
[0003] At present, there are two options to replace CMC: modified CMC and acrylic resin thickener.
[0004] Chinese patent CN115188962A adopts sodium carboxymethyl cellulose and amino groups on sulfonic acid compounds to undergo amide condensation reaction and then graft to obtain modified CMC. The grafting of organic sulfonic acid lithium salt accelerates the migration rate of lithium ions in the electrochemical reaction and can improve the cycle performance of lithium ion batteries, but the test effect of the embodiment is not significantly improved compared with traditional CMC, and there is no mention of whether it can improve the cracking of thick coating of lithium ion battery graphite negative electrode and the effect on peel strength.
[0005] Chinese patent CN113045777A adopts dialdehyde compounds, double-terminal olefin sulfone compounds or double-terminal epoxy polyether compounds to crosslink CMC. Crosslinked CMC can increase viscosity and reduce dosage compared with CMC, but it does not mention whether it can improve the cracking of thick coating of lithium-ion battery graphite negative electrode and the impact on peel strength.
[0006] Chinese patent CN116179121A uses precipitation polymerization to prepare a cross-linked acrylic resin with an acrylic acid content of 96%. The acrylic resin aqueous solution has a very high viscosity and can be used in a smaller amount than CMC. The pole piece peel strength prepared with this resin is partially improved compared to CMC, but this acrylic resin has a high glass transition temperature and is not very effective in improving the cracking of thick coatings on graphite negative electrodes of lithium-ion batteries.
[0007] Chinese patents CN113527572B and CN110982008B both use emulsion polymerization to prepare acrylic emulsions containing reactive surfactants, acrylic monomers, acrylonitrile monomers, acrylamide monomers and acrylate monomers. Both acrylic emulsion thickeners can increase the peel strength of the pole piece and improve the cracking of thick coating of lithium-ion battery graphite negative electrode. However, acrylic emulsions as thickeners cannot match the kneading process during the industrial production of negative electrode slurry.
[0008] Therefore, it is a current challenge to develop an acrylic resin thickener that is simple to synthesize, can improve the cracking of thick coatings on graphite negative electrodes of lithium-ion batteries, and significantly increase the peel strength of the electrode sheets. Summary of the invention
[0009] In order to solve the problem that the pole pieces obtained by the existing thickeners have serious cracking when thickened and poor peeling strength of the pole pieces, the present invention provides an acrylic resin and its preparation method, application, lithium ion battery negative electrode slurry, and negative electrode pole piece. The acrylic resin has good thickening and dispersing performance in the negative electrode slurry system where the active material is graphite, good bonding performance and good flexibility. The lithium ion battery negative electrode pole piece prepared by using the acrylic resin has excellent thick coating anti-cracking performance and can greatly improve the peeling strength of the pole piece.
[0010] In order to achieve the above technical objectives, the present invention adopts the following technical solutions.
[0011] The present invention provides an acrylic resin, the raw materials of which include A-type monomers, B-type monomers, C-type monomers and a crosslinking agent. Taking the total mass of the monomers as 100%, the amount of the A-type monomers is 40% to 70%; the amount of the B-type monomers is 10% to 40%; the amount of the C-type monomers is 10% to 40%; the amount of the crosslinking agent is 0.5% to 3% of the total mass of the monomers;
[0012] The type A monomer is selected from one or more of acrylic acid, maleic anhydride and itaconic acid;
[0013] The B-type monomer is selected from one or more of styrene, α-methylstyrene, acrylonitrile, α-methacrylonitrile, acrylamide, N,N'-dimethylacrylamide, styrene sulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, methyl methacrylate, diacetone acrylamide, ethyl acetoacetate methacrylate, ethoxyethoxyethyl acrylate, tetrahydrofurfuryl acrylate, cyclotrimethylolpropane formal acrylate, N-(N-butoxymethyl)acrylamide, 2-phenoxyethyl acrylate, vinyl acetate and polyethylene glycol monomethyl ether acrylate;
[0014] The C-type monomer is selected from one or more of ethyl acrylate, butyl acrylate, isooctyl acrylate, lauryl acrylate, octadecyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxybutyl acrylate and carboxyethyl acrylate;
[0015] The crosslinking agent is selected from one or more of diallyl phthalate, N,N'-methylenebisacrylamide, ethylene glycol diacrylate, tripropylene glycol diacrylate, 1,4-butanediol acrylate and 1,6-hexanediol diacrylate.
[0016] In the present invention, the usage of the type A monomer is preferably 50% to 70%, more preferably 60% to 70%.
[0017] In the present invention, the usage of the B-type monomer is preferably 25% to 35%, for example 30%.
[0018] In the present invention, the usage of the C-type monomer is preferably 10% to 30%, for example 20%.
[0019] In the present invention, the amount of the crosslinking agent is preferably 0.5% to 2%, more preferably 1% to 2%, for example 1.5% or 2%.
[0020] In some specific embodiments, the amount of the type A monomer is 40%, the amount of the type B monomer is 40%, the amount of the type C monomer is 20%, and the amount of the cross-linking agent is 1.5%.
[0021] In some specific embodiments, the amount of the type A monomer is 50%, the amount of the type B monomer is 30%, the amount of the type C monomer is 20%, and the amount of the cross-linking agent is 2%.
[0022] In some specific embodiments, the amount of the type A monomer is 60%, the amount of the type B monomer is 30%, the amount of the type C monomer is 10%, and the amount of the cross-linking agent is 2%.
[0023] In some specific embodiments, the amount of the type A monomer is 70%, the amount of the type B monomer is 20%, the amount of the type C monomer is 10%, and the amount of the cross-linking agent is 2%.
[0024] In some specific embodiments, the amount of the type A monomer is 60%, the amount of the type B monomer is 20%, the amount of the type C monomer is 20%, and the amount of the cross-linking agent is 2%.
[0025] In the present invention, preferably, the type A monomer is selected from acrylic acid, maleic anhydride or itaconic acid.
[0026] In the present invention, preferably, the B-type monomer is selected from two of styrene, acrylonitrile, acrylamide, N,N'-dimethylacrylamide, styrene sulfonic acid, 2-acrylamido-2-methylpropane sulfonic acid, methyl methacrylate, diacetone acrylamide, ethyl methyl acetoacetate, ethoxyethoxyethyl acrylate, tetrahydrofurfuryl acrylate, cyclotrimethylolpropane formal acrylate, N-(N-butoxymethyl)acrylamide, 2-phenoxyethyl acrylate, vinyl acetate and polyethylene glycol monomethyl ether acrylate; more preferably, the two monomers are of different types.
[0027] In some preferred embodiments, the B-type monomers are acrylamide and styrene sulfonic acid, N,N'-dimethylacrylamide and tetrahydrofurfuryl acrylate, ethyl acetoacetate methacrylate and ethoxyethoxyethyl acrylate, acrylonitrile and methyl methacrylate, styrene and 2-acrylamido-2-methylpropane sulfonic acid, cyclotrimethylolpropane formal acrylate and N-(N-butoxymethyl)acrylamide, 2-phenoxyethyl acrylate and acrylonitrile, 2-acrylamido-2-methylpropane sulfonic acid and acrylamide, vinyl acetate and polyethylene glycol monomethyl ether acrylate, or tetrahydrofurfuryl acrylate and diacetone acrylamide.
[0028] Among them, more preferably, the mass ratio of the two monomers in the B-type monomers is preferably 1:(0.5-3), more preferably 1:(0.5-2), for example 1:1.
[0029] In the present invention, the C-type monomer is preferably ethyl acrylate, butyl acrylate, isooctyl acrylate, lauryl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxybutyl acrylate or carboxyethyl acrylate.
[0030] In some specific embodiments, the type A monomer is acrylic acid, the type B monomer is acrylamide and styrene sulfonic acid, the type C monomer is hydroxybutyl acrylate, and the crosslinking agent is diallyl phthalate.
[0031] In some specific embodiments, the type A monomer is acrylic acid, the type B monomer is N,N'-dimethylacrylamide and tetrahydrofurfuryl acrylate, the type C monomer is hydroxyethyl acrylate, and the crosslinking agent is N,N'-methylenebisacrylamide.
[0032] In some specific embodiments, the type A monomer is acrylic acid, the type B monomer is ethyl acetoacetate methacrylate and ethoxyethoxyethyl acrylate, the type C monomer is hydroxypropyl acrylate, and the crosslinking agent is ethylene glycol diacrylate.
[0033] In some specific embodiments, the type A monomer is acrylic acid, the type B monomer is acrylonitrile and methyl methacrylate, the type C monomer is ethyl acrylate, and the cross-linking agent is ethylene glycol diacrylate.
[0034] In some specific embodiments, the type A monomer is maleic anhydride, the type B monomer is styrene and 2-acrylamido-2-methylpropanesulfonic acid, the type C monomer is butyl acrylate, and the crosslinking agent is N,N'-methylenebisacrylamide.
[0035] In some specific embodiments, the type A monomer is maleic anhydride, the type B monomer is cyclotrimethylolpropane formal acrylate and N-(N-butoxymethyl)acrylamide, the type C monomer is isooctyl acrylate, and the crosslinking agent is N,N'-methylenebisacrylamide.
[0036] In some specific embodiments, the monomer of type A is itaconic acid, the monomer of type B is 2-phenoxyethyl acrylate and acrylonitrile, the monomer of type C is hydroxyethyl acrylate, and the crosslinking agent is N,N'-methylenebisacrylamide.
[0037] In some specific embodiments, the monomer of type A is itaconic acid, the monomer of type B is 2-acrylamido-2-methylpropanesulfonic acid and acrylamide, the monomer of type C is hydroxybutyl acrylate, and the crosslinking agent is N,N'-methylenebisacrylamide.
[0038] In some specific embodiments, the type A monomer is acrylic acid, the type B monomer is vinyl acetate and polyethylene glycol monomethyl ether acrylate, the type C monomer is carboxyethyl acrylate, and the cross-linking agent is ethylene glycol diacrylate.
[0039] In some specific embodiments, the type A monomer is acrylic acid, the type B monomer is tetrahydrofurfuryl acrylate and diacetone acrylamide, the type C monomer is lauryl acrylate, and the crosslinking agent is ethylene glycol diacrylate.
[0040] In the present invention, the method for preparing the acrylic resin preferably comprises the following steps:
[0041] a. mixing the type A monomer, the first solvent and the base to obtain a first mixed solution;
[0042] b. Adding the B monomer, C monomer, crosslinking agent and second solvent to the first mixed solution to obtain a pre-reaction solution, and adding the initiator and the second mixed solution of the third solvent to the pre-reaction solution to carry out polymerization reaction; wherein the polymerization reaction temperature is 70-80°C.
[0043] In step a, the base may be an alkali metal hydroxide. The alkali metal oxide preferably includes one or more of lithium hydroxide, sodium hydroxide and potassium hydroxide.
[0044] In step a, the first solvent is preferably an alcohol solvent. The alcohol solvent is preferably one or more of methanol, ethanol, propanol, isopropanol and ethylene glycol.
[0045] In step a, in the mixed solution, the molar ratio of the type A monomer to the base is preferably (0.5-1.5):1, for example, 1:1.
[0046] In step a, the mixing temperature of the first mixed solution is preferably 45-55°C, for example 50°C.
[0047] In step a, the mixing time of the first mixed solution is preferably 1 to 3 hours, more preferably 1.5 to 2.5 hours, for example 1 hour.
[0048] In step b, the polymerization reaction temperature is preferably 75-80°C.
[0049] In step b, before adding the type B monomer, the type C monomer, the cross-linking agent and the second solvent to the first mixed solution to obtain the pre-reaction solution, preferably, the first mixed solution is first heated to the polymerization reaction temperature.
[0050] In step b, the polymerization reaction time is preferably 2-4 hours, for example 3 hours.
[0051] In step b, the second solvent is preferably an alcohol solvent. The alcohol solvent is preferably one or more of methanol, ethanol, propanol, isopropanol and ethylene glycol.
[0052] In step b, the amount of the second solvent is preferably 40% to 70%, for example 50%, where the percentage is the mass percentage of the total mass of the monomers.
[0053] In step b, the initiator is preferably selected from one or more of azobisisoheptanitrile, azobisisobutyronitrile and benzoyl peroxide, for example, azobisisobutyronitrile.
[0054] In step b, the amount of the initiator is preferably 0.2% to 1.2%, for example 0.5%, where the percentage is the mass percentage of the total mass of the monomers.
[0055] In step b, the third solvent is preferably an alcohol solvent. The alcohol solvent is preferably one or more of methanol, ethanol, propanol, isopropanol and ethylene glycol.
[0056] In step b, in the second mixed solution, the mass ratio of the initiator to the third solvent is preferably (0.2-1.2):(40-70), for example, 0.5:50.
[0057] In step b, the second mixed solution is preferably added dropwise.
[0058] The dropping time is preferably 1 to 3 hours, for example 2 hours.
[0059] In the present invention, during the polymerization reaction, after adding the second mixed solution of the initiator and the third solvent, an operation of keeping the temperature at the polymerization reaction temperature may be further included.
[0060] The insulation time is preferably 1 to 3 hours, for example 1 hour.
[0061] The insulation temperature is preferably 70-80°C, for example 75°C.
[0062] The present invention provides a method for preparing the acrylic resin as described above, which comprises the following steps:
[0063] a. mixing the type A monomer, the first solvent and the base to obtain a first mixed solution;
[0064] b. Adding the B monomer, C monomer, crosslinking agent and second solvent to the first mixed solution to obtain a pre-reaction solution, and adding the initiator and the second mixed solution of the third solvent to the pre-reaction solution to carry out polymerization reaction; wherein the polymerization reaction temperature is 70-80°C.
[0065] In the present invention, the steps and conditions of the preparation method of the acrylic resin are as described above.
[0066] The present invention provides a use of the acrylic resin as described above as a thickener in a lithium ion battery.
[0067] The present invention provides a lithium ion battery negative electrode slurry, which comprises the acrylic resin as described above.
[0068] Preferably, the lithium-ion battery negative electrode slurry further comprises graphite, a conductive agent and a binder.
[0069] The usage of the acrylic resin is preferably 1% to 3%, where the percentage is the mass percentage of the negative electrode slurry of the lithium-ion battery.
[0070] The amount of graphite used is preferably 95% to 97%, where the percentage is the mass percentage of the negative electrode slurry of the lithium-ion battery.
[0071] The amount of the conductive agent is preferably 0.5% to 2%, where the percentage is the mass percentage of the negative electrode slurry of the lithium-ion battery.
[0072] The amount of the binder is preferably 1% to 3%, where the percentage is the mass percentage of the negative electrode slurry of the lithium-ion battery.
[0073] In some specific embodiments, the amount of the acrylic resin is 1.2%, the amount of the graphite is 96.3%, the amount of the conductive agent is 1%, and the amount of the binder is 1.5%, where the percentages are the mass percentages of each component in the negative electrode slurry of the lithium ion battery.
[0074] The present invention also provides a lithium ion battery negative electrode plate, which comprises the acrylic resin as described above.
[0075] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0076] The reagents and raw materials used in the present invention are commercially available.
[0077] The positive and progressive effects of the present invention are:
[0078] (1) The acrylic resin in the present invention is prepared by a precipitation polymerization method, and no dispersant needs to be added during the polymerization process. The obtained acrylic resin has good adhesion and flexibility. As a thickener, it can achieve good thickening and dispersing effects in a negative electrode slurry system in which the active material is graphite, so that the negative electrode plate prepared by using the thickener has excellent thick coating anti-cracking performance and can greatly improve the peel strength of the plate.
[0079] (2) The acrylic resin prepared by the present invention has excellent performance as a thickener, low raw material cost, and simple synthesis. It can completely replace the traditional thickener CMC and has a good application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0080] Figure 1 The figure is a comparison diagram of the cracking conditions of the negative electrode sheets obtained in Example 2 using the acrylic resin prepared in Example 1 and the CMC in Comparative Example 1 as thickeners. DETAILED DESCRIPTION
[0081] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0082] Example 1
[0083] The preparation method of acrylic resin in this embodiment comprises the following steps:
[0084] a. Add 40 parts of acrylic acid and 1:1 molar ratio of sodium hydroxide to 300 parts of isopropanol and react at 50°C for 1 hour;
[0085] b. Raise the temperature to 75 ° C, add 20 parts of acrylamide, 20 parts of styrene sulfonic acid, 20 parts of hydroxybutyl acrylate and 1.5 parts of diallyl phthalate and 50 parts of isopropanol to the reaction system, and dropwise add 0.5 parts of azobisisobutyronitrile and 30 parts of isopropanol to form a solution for polymerization;
[0086] c. Add dropwise for 2 hours, keep warm at 75°C for 1 hour, filter after polymerization is complete, and dry to obtain.
[0087] Example 2
[0088] The preparation method of acrylic resin in this embodiment comprises the following steps:
[0089] a. Add 50 parts of acrylic acid and lithium hydroxide in a molar ratio of 1:1 to 300 parts of ethanol and react at 50°C for 1 hour;
[0090] b. Raise the temperature to 75 ° C, add 10 parts of N, N'- dimethyl acrylamide, 20 parts of tetrahydrofurfuryl acrylate, 20 parts of hydroxyethyl acrylate and 2 parts of N, N'- methylenebisacrylamide and 50 parts of ethanol to the reaction system, and dropwise add 0.5 parts of azobisisobutyronitrile and 30 parts of ethanol to form a solution for polymerization;
[0091] c. Add dropwise for 2 hours, keep warm at 75°C for 1 hour, filter after polymerization is complete, and dry to obtain.
[0092] Example 3
[0093] The preparation method of acrylic resin in this embodiment comprises the following steps:
[0094] a. Add 60 parts of acrylic acid and potassium hydroxide in a molar ratio of 1:1 to 300 parts of ethylene glycol and react at 50°C for 1 hour;
[0095] b. Raise the temperature to 75 ° C, add 20 parts of ethyl methacrylate, 10 parts of ethoxyethoxyethyl acrylate, 10 parts of hydroxypropyl acrylate, 2 parts of ethylene glycol diacrylate and 50 parts of ethylene glycol to the reaction system, and add 0.5 parts of azobisisobutyronitrile and 30 parts of ethylene glycol to form a solution to polymerize;
[0096] c. Add dropwise for 2 hours, keep warm at 75°C for 1 hour, filter after polymerization is complete, and dry to obtain.
[0097] Example 4
[0098] The preparation method of acrylic resin in this embodiment comprises the following steps:
[0099] a. Add 70 parts of acrylic acid and potassium hydroxide in a molar ratio of 1:1 to 300 parts of ethanol and react at 50°C for 1 hour;
[0100] b. Raise the temperature to 75 ° C, add 10 parts of acrylonitrile, 10 parts of methyl methacrylate, 10 parts of ethyl acrylate and 2 parts of ethylene glycol diacrylate and 50 parts of ethanol to the reaction system, and add dropwise 0.5 parts of azobisisobutyronitrile and 30 parts of ethanol to form a solution for polymerization;
[0101] c. Add dropwise for 2 hours, keep warm at 75°C for 1 hour, filter after polymerization is complete, and dry to obtain.
[0102] Example 5
[0103] The preparation method of acrylic resin in this embodiment comprises the following steps:
[0104] a. Add 50 parts of maleic anhydride and potassium hydroxide in a molar ratio of 1:1 to 300 parts of ethanol and react at 50°C for 1 hour;
[0105] b. Raise the temperature to 75 ° C, add 10 parts of styrene, 20 parts of 2-acrylamido-2-methylpropanesulfonic acid, 20 parts of butyl acrylate and 2 parts of N, N'-methylenebisacrylamide and 50 parts of ethanol to the reaction system, and dropwise add 0.5 parts of azobisisobutyronitrile and 30 parts of ethanol to form a solution for polymerization;
[0106] c. Add dropwise for 2 hours, keep warm at 75°C for 1 hour, filter after polymerization is complete, and dry to obtain.
[0107] Example 6
[0108] The preparation method of acrylic resin in this embodiment comprises the following steps:
[0109] a. Add 60 parts of maleic anhydride and lithium hydroxide in a molar ratio of 1:1 to 300 parts of ethanol and react at 50°C for 1 hour;
[0110] b. Raise the temperature to 75 ° C, add 10 parts of cyclotrimethylolpropane formal acrylate, 10 parts of N-(N-butoxymethyl) acrylamide, 20 parts of isooctyl acrylate and 2 parts of N, N'-methylenebisacrylamide and 50 parts of ethanol to the reaction system, and dropwise add 0.5 parts of azobisisobutyronitrile and 30 parts of ethanol to form a solution for polymerization;
[0111] c. Add dropwise for 2 hours, keep warm at 75°C for 1 hour, filter after polymerization is complete, and dry to obtain.
[0112] Example 7
[0113] The preparation method of acrylic resin in this embodiment comprises the following steps:
[0114] a. Add 50 parts of itaconic acid and lithium hydroxide in a molar ratio of 1:1 to 300 parts of ethanol and react at 50°C for 1 hour;
[0115] b. Raise the temperature to 75 ° C, add 10 parts of 2-phenoxyethyl acrylate, 20 parts of acrylonitrile, 20 parts of hydroxyethyl acrylate and 2 parts of N, N'-methylenebisacrylamide and 50 parts of ethanol to the reaction system, and add 0.5 parts of azobisisobutyronitrile and 30 parts of ethanol to form a solution to polymerize;
[0116] c. Add dropwise for 2 hours, keep warm at 75°C for 1 hour, filter after polymerization is complete, and dry to obtain.
[0117] Example 8
[0118] The preparation method of acrylic resin in this embodiment comprises the following steps:
[0119] a. Add 60 parts of itaconic acid and 1:1 molar ratio of lithium hydroxide to 300 parts of ethanol and react at 50°C for 1 hour;
[0120] b. Raise the temperature to 75 ° C, add 10 parts of 2-acrylamido-2-methylpropanesulfonic acid, 10 parts of acrylamide, 20 parts of hydroxybutyl acrylate and 2 parts of N, N'-methylenebisacrylamide and 50 parts of ethanol to the reaction system, and dropwise add 0.5 parts of azobisisobutyronitrile and 30 parts of ethanol to form a solution for polymerization;
[0121] c. Add dropwise for 2 hours, keep warm at 75°C for 1 hour, filter after polymerization is complete, and dry to obtain.
[0122] Example 9
[0123] The preparation method of acrylic resin in this embodiment comprises the following steps:
[0124] a. Add 50 parts of acrylic acid and lithium hydroxide in a molar ratio of 1:1 to 300 parts of ethanol and react at 50°C for 1 hour;
[0125] b. Raise the temperature to 75 ° C, add 20 parts of vinyl acetate, 10 parts of polyethylene glycol monomethyl ether acrylate, 20 parts of carboxyethyl acrylate and 2 parts of ethylene glycol diacrylate and 50 parts of ethanol to the reaction system, and add dropwise 0.5 parts of azobisisobutyronitrile and 30 parts of ethanol to form a solution for polymerization;
[0126] c. Add dropwise for 2 hours, keep warm at 75°C for 1 hour, filter after polymerization is complete, and dry to obtain.
[0127] Example 10
[0128] a. Add 50 parts of acrylic acid and lithium hydroxide in a molar ratio of 1:1 to 300 parts of ethanol and react at 50°C for 1 hour;
[0129] b. Raise the temperature to 75 ° C, add 10 parts of tetrahydrofurfuryl acrylate, 20 parts of diacetone acrylamide, 20 parts of lauryl acrylate and 2 parts of N, N'-methylenebisacrylamide and 50 parts of ethanol to the reaction system, and add 0.5 parts of azobisisobutyronitrile and 30 parts of ethanol to form a solution to polymerize;
[0130] c. Add dropwise for 2 hours, keep warm at 75°C for 1 hour, filter after polymerization is complete, and dry to obtain.
[0131] Comparative Example 1
[0132] A conventional CMC (purchased from Ashland, model BVH9) was used.
[0133] Some parameters of the above Examples 1-10 and Comparative Example 1 are shown in Table 1.
[0134] Table 1
[0135]
[0136]
[0137] Effect Example 1
[0138] The acrylic resins prepared in Examples 1 to 10 and the CMC in Comparative Example 1 were used as thickeners to prepare negative electrode slurries. The viscosity of the slurries was tested. The results are shown in Table 2.
[0139] The method for preparing the negative electrode slurry comprises the following steps:
[0140] In terms of mass percentage (total mass is 100%), the dry materials of the slurry are composed of: 96.3% artificial graphite, 1.2% thickener, 1.5% SBR, and 1% conductive carbon black. According to the above amounts, the above slurry dry materials are added with water and mixed to obtain a negative electrode slurry (solid content is 50%).
[0141] The slurry viscosity is obtained by testing the negative electrode slurry prepared above using a rotational viscometer.
[0142] It can be seen from Table 2 that, compared with Comparative Example 1 using conventional CMC as a thickener, the viscosity of the negative electrode slurries prepared using acrylic resin as a thickener in Examples 1 to 10 are suitable for coating and have good processing performance.
[0143] Table 2 Viscosity of negative electrode slurry obtained by using acrylic resin as thickener in Examples 1 to 10 and CMC in Comparative Example 1
[0144]
[0145]
[0146] Effect Example 2
[0147] Based on the negative electrode slurry prepared in Example 1, a negative electrode sheet was prepared. The electrode sheets obtained in Example 1 and Comparative Example 1 were photographed to obtain the cracking conditions thereof as shown in FIG. Figure 1 shown.
[0148] The method for preparing the negative electrode sheet comprises the following steps:
[0149] The prepared negative electrode slurry is coated on the negative electrode current collector copper foil, dried and rolled to obtain a negative electrode sheet, and the negative electrode slurry forms an active material layer. The compaction density of the negative electrode sheet is 1.67 g / cm 3 .
[0150] from Figure 1 It can be seen that the negative electrode sheet prepared by using the acrylic resin in Example 1 as a thickener has obvious anti-cracking performance compared with the negative electrode sheet prepared by using the traditional CMC as a thickener.
[0151] Effect Example 3
[0152] Based on the negative electrode sheet prepared in Effect Example 2, the sheet peeling performance was tested, and the test results are shown in Table 3.
[0153] Among them, the test method for the peeling performance of the negative electrode plate includes the following steps: bonding one side of the active material layer of the negative electrode plate to the steel plate through double-sided tape, and performing a 180° peeling test using an electronic universal testing machine.
[0154] Table 3 Peel strength of negative electrode sheet
[0155]
[0156]
[0157] As shown in Table 3, the peel strength of the negative electrode sheets prepared using the acrylic resin obtained in Examples 1 to 10 as a thickener can reach above 13 N / m, which is significantly better than the peel strength of the negative electrode sheets prepared using traditional CMC in Comparative Example 1.
[0158] It can be seen from the effect examples 2 and 3 that the negative electrode sheets prepared by using the acrylic resins of examples 1 to 10 of the present invention as thickeners have an anti-cracking effect while improving the peeling strength of the sheets. This may be because the acrylic resins of the present invention are designed with polyelectrolyte structures and a large number of hydrogen bond structures, which can achieve thickening and dispersion effects; and a variety of polar groups are used in the molecular design, so that the polymer has a high cohesive force and a high interfacial adhesion, achieving a balance between a rigid structure and a flexible structure.
[0159] Although the specific embodiments of the present invention are described above, those skilled in the art should understand that this is only an example, and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without violating the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. An acrylic resin, characterized in that The raw materials include A-type monomers, B-type monomers, C-type monomers and crosslinking agents. Taking the total mass of the monomers as 100%, the amount of the A-type monomers is 40% to 70%; the amount of the B-type monomers is 10% to 40%; the amount of the C-type monomers is 10% to 40%; and the amount of the crosslinking agent is 0.5% to 3% of the total mass of the monomers. The type A monomer is selected from one or more of acrylic acid, maleic anhydride and itaconic acid; The B-type monomer is selected from one or more of styrene, α-methylstyrene, acrylonitrile, α-methacrylonitrile, acrylamide, N,N'-dimethylacrylamide, styrene sulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, methyl methacrylate, diacetone acrylamide, ethyl acetoacetate methacrylate, ethoxyethoxyethyl acrylate, tetrahydrofurfuryl acrylate, cyclotrimethylolpropane formal acrylate, N-(N-butoxymethyl)acrylamide, 2-phenoxyethyl acrylate, vinyl acetate and polyethylene glycol monomethyl ether acrylate; The C-type monomer is selected from one or more of ethyl acrylate, butyl acrylate, isooctyl acrylate, lauryl acrylate, octadecyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxybutyl acrylate and carboxyethyl acrylate; The crosslinking agent is selected from one or more of diallyl phthalate, N,N'-methylenebisacrylamide, ethylene glycol diacrylate, tripropylene glycol diacrylate, 1,4-butanediol acrylate and 1,6-hexanediol diacrylate.
2. The acrylic resin according to claim 1, characterized in that The amount of the type A monomer is 50% to 70%, preferably 60% to 70%; And / or, the amount of the B-type monomer is 25% to 35%, for example, 30%; And / or, the amount of the C-type monomer is 10% to 30%, for example, 20%; And / or, the amount of the cross-linking agent is 0.5% to 2%, preferably 1% to 2%, for example 1.5% or 2%; and / or, the type A monomer is selected from acrylic acid, maleic anhydride or itaconic acid; and / or, the B-type monomer is selected from two of styrene, acrylonitrile, acrylamide, N,N'-dimethylacrylamide, styrene sulfonic acid, 2-acrylamido-2-methylpropane sulfonic acid, methyl methacrylate, diacetone acrylamide, ethyl acetoacetate methacrylate, ethoxyethoxyethyl acrylate, tetrahydrofurfuryl acrylate, cyclotrimethylolpropane formal acrylate, N-(N-butoxymethyl)acrylamide, 2-phenoxyethyl acrylate, vinyl acetate and polyethylene glycol monomethyl ether acrylate; preferably, the two monomers are of different types; Preferably, the B-type monomer is acrylamide and styrene sulfonic acid, N,N'-dimethylacrylamide and tetrahydrofurfuryl acrylate, ethyl acetoacetate methacrylate and ethoxyethoxyethyl acrylate, acrylonitrile and methyl methacrylate, styrene and 2-acrylamido-2-methylpropane sulfonic acid, cyclotrimethylolpropane formal acrylate and N-(N-butoxymethyl)acrylamide, 2-phenoxyethyl acrylate and acrylonitrile, 2-acrylamido-2-methylpropane sulfonic acid and acrylamide, vinyl acetate and polyethylene glycol monomethyl ether acrylate, or tetrahydrofurfuryl acrylate and diacetone acrylamide; Among them, more preferably, the mass ratio of the two monomers in the B-type monomer is preferably 1:(0.5-3), more preferably 1:(0.5-2), for example, 1:1; And / or, the C-type monomer is ethyl acrylate, butyl acrylate, isooctyl acrylate, lauryl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxybutyl acrylate or carboxyethyl acrylate.
3. The acrylic resin according to claim 1, characterized in that The types of the class A monomer, class B monomer, class C monomer and cross-linking agent are any of the following: The class A monomer is acrylic acid, the class B monomer is acrylamide and styrene sulfonic acid, the class C monomer is hydroxybutyl acrylate, and the cross-linking agent is diallyl phthalate; Alternatively, the class A monomer is acrylic acid, the class B monomer is N,N'-dimethylacrylamide and tetrahydrofurfuryl acrylate, the class C monomer is hydroxyethyl acrylate, and the crosslinking agent is N,N'-methylenebisacrylamide; Alternatively, the class A monomer is acrylic acid, the class B monomer is ethyl acetoacetate methacrylate and ethoxyethoxyethyl acrylate, the class C monomer is hydroxypropyl acrylate, and the cross-linking agent is ethylene glycol diacrylate; Alternatively, the class A monomer is acrylic acid, the class B monomer is acrylonitrile and methyl methacrylate, the class C monomer is ethyl acrylate, and the cross-linking agent is ethylene glycol diacrylate; Alternatively, the class A monomer is maleic anhydride, the class B monomer is styrene and 2-acrylamido-2-methylpropanesulfonic acid, the class C monomer is butyl acrylate, and the crosslinking agent is N,N'-methylenebisacrylamide; Alternatively, the class A monomer is maleic anhydride, the class B monomer is cyclotrimethylolpropane formal acrylate and N-(N-butoxymethyl)acrylamide, the class C monomer is isooctyl acrylate, and the crosslinking agent is N,N'-methylenebisacrylamide; Alternatively, the class A monomer is itaconic acid, the class B monomer is 2-phenoxyethyl acrylate and acrylonitrile, the class C monomer is hydroxyethyl acrylate, and the crosslinking agent is N,N'-methylenebisacrylamide; Alternatively, the class A monomer is itaconic acid, the class B monomer is 2-acrylamido-2-methylpropanesulfonic acid and acrylamide, the class C monomer is hydroxybutyl acrylate, and the crosslinking agent is N,N'-methylenebisacrylamide; Alternatively, the class A monomer is acrylic acid, the class B monomer is vinyl acetate and polyethylene glycol monomethyl ether acrylate, the class C monomer is carboxyethyl acrylate, and the cross-linking agent is ethylene glycol diacrylate; Alternatively, the class A monomer is acrylic acid, the class B monomer is tetrahydrofurfuryl acrylate and diacetone acrylamide, the class C monomer is lauryl acrylate, and the cross-linking agent is ethylene glycol diacrylate; And / or, the dosage of the class A monomer, the class B monomer, the class C monomer and the cross-linking agent is any one of the following: The amount of the class A monomer is 40%, the amount of the class B monomer is 40%, the amount of the class C monomer is 20%, and the amount of the cross-linking agent is 1.5%; Alternatively, the amount of the class A monomer is 50%, the amount of the class B monomer is 30%, the amount of the class C monomer is 20%, and the amount of the cross-linking agent is 2%; Alternatively, the amount of the class A monomer is 60%, the amount of the class B monomer is 30%, the amount of the class C monomer is 10%, and the amount of the cross-linking agent is 2%; Alternatively, the amount of the class A monomer is 70%, the amount of the class B monomer is 20%, the amount of the class C monomer is 10%, and the amount of the cross-linking agent is 2%; Alternatively, the usage of the type A monomer is 60%, the usage of the type B monomer is 20%, the usage of the type C monomer is 20%, and the usage of the cross-linking agent is 2%.
4. The acrylic resin according to any one of claims 1 to 3, characterized in that The preparation method of the acrylic resin comprises the following steps: a. mixing the type A monomer, the first solvent and the base to obtain a first mixed solution; b. Adding the B monomer, C monomer, crosslinking agent and second solvent to the first mixed solution to obtain a pre-reaction solution, and adding the initiator and the second mixed solution of the third solvent to the pre-reaction solution to carry out polymerization reaction; wherein the polymerization reaction temperature is 70-80°C.
5. The acrylic resin according to claim 4, characterized in that In step a, The base is an alkali metal hydroxide, and the alkali metal oxide preferably includes one or more of lithium hydroxide, sodium hydroxide and potassium hydroxide; And / or, in step a, the first solvent is an alcohol solvent; the alcohol solvent is preferably one or more of methanol, ethanol, propanol, isopropanol and ethylene glycol; And / or, in step a, in the first mixed solution, the molar ratio of the type A monomer to the base is (0.5-1.5):1, for example, 1:1; And / or, in step a, the mixing temperature of the first mixed solution is 45-55° C., for example, 50° C.; And / or, in step a, the mixing time of the first mixed solution is 1 to 3 hours, preferably 1.5 to 2.5 hours, for example 1 hour; And / or, in step b, the polymerization reaction temperature is 75-80°C; And / or, in step b, the polymerization reaction time is 2-4 hours, for example, 3 hours; And / or, in step b, before adding the type B monomer, the type C monomer, the cross-linking agent and the second solvent to the first mixed solution to obtain the pre-reaction solution, the first mixed solution is first heated to the polymerization reaction temperature; And / or, in step b, the second solvent is an alcohol solvent; the alcohol solvent is preferably one or more of methanol, ethanol, propanol, isopropanol and ethylene glycol; And / or, in step b, the amount of the second solvent is 40% to 70%, for example, 50%, where the percentage is the mass percentage of the total mass of the monomers; And / or, in step b, the initiator is selected from one or more of azobisisoheptanonitrile, azobisisobutyronitrile and benzoyl peroxide, for example, azobisisobutyronitrile; And / or, in step b, the amount of the initiator is 0.2% to 1.2%, for example, 0.5%, where the percentage is the mass percentage of the total mass of the monomers; And / or, in step b, the third solvent is an alcohol solvent; the alcohol solvent is preferably one or more of methanol, ethanol, propanol, isopropanol and ethylene glycol; And / or, in step b, in the second mixed solution, the mass ratio of the initiator to the third solvent is (0.2-1.2):(40-70), for example, 0.5:50; And / or, in step b, the second mixed solution is added dropwise; Preferably, the dripping time is 1 to 3 hours, for example, 2 hours; And / or, during the polymerization reaction, after adding the second mixed solution of the initiator and the third solvent, the process also includes an insulation operation at the temperature of the polymerization reaction; wherein the insulation time is preferably 1 to 3 hours, for example, 1 hour; the insulation temperature is preferably 70-80°C, for example, 75°C.
6. A method for preparing an acrylic resin as claimed in any one of claims 1 to 5, characterized in that: It includes the following steps: a. mixing the type A monomer, the first solvent and the base to obtain a first mixed solution; b. Adding the B monomer, C monomer, crosslinking agent and second solvent to the first mixed solution to obtain a pre-reaction solution, and adding the initiator and the second mixed solution of the third solvent to the pre-reaction solution to carry out polymerization reaction; wherein the polymerization reaction temperature is 70-80°C.
7. The method for preparing an acrylic resin according to claim 6, wherein: The steps and conditions of the method for preparing the acrylic resin are as described in claim 4 or 5.
8. Use of the acrylic resin according to any one of claims 1 to 5 as a thickener in a lithium ion battery.
9. A negative electrode slurry for a lithium ion battery, characterized in that: It comprises an acrylic resin as described in any one of claims 1 to 5; Preferably, the lithium-ion battery negative electrode slurry further comprises graphite, a conductive agent and a binder; Among them, the amount of the acrylic resin is preferably 1% to 3%; the amount of the graphite is preferably 95% to 97%; the amount of the conductive agent is preferably 0.5% to 2%; the amount of the binder is preferably 1% to 3%; the percentage is the mass percentage of each component in the negative electrode slurry of the lithium ion battery; More preferably, the amount of the acrylic resin is 1.2%, the amount of the graphite is 96.3%, the amount of the conductive agent is 1%, and the amount of the binder is 1.5%.
10. A negative electrode plate for a lithium ion battery, characterized in that: It comprises the acrylic resin as claimed in any one of claims 1 to 5.
Citation Information
Patent Citations
Aqueous binder for lithium-ion battery negative electrode
CN110982008B
Negative electrode dispersing agent and lithium ion battery containing dispersing agent
CN113045777A
A water-based thickener / dispersant and a water-based binder for lithium-ion batteries and their preparation method
CN113527572B
Lithium ion battery negative electrode dispersing agent as well as preparation method and application thereof
CN115188962A
Lithium ion battery negative electrode binder, preparation method thereof and negative electrode slurry
CN116179121A
Cited By
Copolymer for lithium ion battery, negative pole piece and preparation and application methods of copolymer and negative pole piece
CN121471417A
Aqueous binder for negative electrode of lithium ion battery as well as preparation method and application of aqueous binder
CN122255909A